Haematococcus pluvialis derived astaxanthin – a powerful bioactive compound for vegetable oils - RUDI, Ludmila; PLINGAU, Ecaterina; MISCU, Vera (One Health & Risk Management, 2024)
Introduction: The beneficial effects on health result from the protective action of astaxanthin (AXT) as a powerful antioxidant capable of scavenging free radicals and protecting cells from oxidative stress. The study aimed to evaluate the protective role of astaxanthin derived from Haematococcus pluvialis in reducing the thermal oxidation of fatty acids in vegetable oils. Material and Methods: Astaxanthin, obtained by extraction from the biomass of Haematococcus pluvialis, at a concentration of 0.26-0.29 mg/mL, was added to olive, sunflower, almond, walnut, sesame, and poppy seed oils. The progression of oxidation was monitored based on the formation of conjugated dienes. The formation of conjugated dienes was monitored spectrophotometrically.Results: Astaxanthin reduced the content of conjugated dienes in sesame, almond, and walnut oils by 30-34%. A strong antioxidant effect of AXT was noted in the case of poppy seed oil, for which the formation of conjugated dienes was decreased by 42% and the oxidation was delayed by 60 min when exposed to high temperatures compared to native oil. For sunflower oil, which exhibited a high degree of thermal oxidation, addition of AXT reduced the formation of conjugated dienes by 22% during the experiment.Conclusions: Astaxanthin from Haematococcus pluvialis significantly reduced the formation of conjugated dienes, indicating it does not act as a prooxidant in various vegetable oils.